Cyprus : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report ;, 2022)
Cyprus is highly exposed to the fallout from the war in Ukraine through trade with Russia. This new challenge comes against the background of the lingering effects of the pandemic and financial vulnerabilities dating from the 2012-13 crisis. Growth is projected to slow from 5 1/2 percent in 2021 to around 2 percent this year. Recovery will regain momentum in 2023, and is projected to continue in the medium term, supported by investments and structural reforms in the Recovery and Resilience Plan.